The implementation of arbitral award annulment in judicial practice - Hetty Maria Pasaribu; Dhaniswara K Harjono; Bernard Nainggolan (Trigin Publisher, 2026)
This research examines the mechanism for the annulment of arbitral awards in Indonesia under Law No. 30 of 1999. Although arbitral awards are inherently final and binding, positive law provides an avenue for annulment through the District Court based on the limited grounds specified in Article 70. The primary legal issue arises from the dualism in judicial views regarding the availability of Civil Review (PK) against such annulment decisions. Utilizing a normative legal research method, this study analyzes the ratio legis of annulment regulations and the implications of Supreme Court Circular (SEMA) No. 4 of 2016. The findings indicate that the Circular strictly prohibits Civil Review to ensure swifter legal certainty and business efficiency. However, the annulment mechanism still carries risks regarding the loss of confidentiality and potential time inefficiency for the parties. The author concludes that courts must adhere to the principle of minimal intervention, where annulment is granted only under extraordinary conditions without re-examining the merits of the case, to maintain the integrity of arbitration as a trusted dispute resolution institution for the international business community.